(untitled) (CIPEEX, 2025)
Patients with COPD often present cardiovascular complications such as pulmonary hypertension, arrhythmias, and right ventricular dysfunction, which can worsen heart failure. Proper management of COPD includes optimizing lung function and treating associated cardiovascular conditions. The treatment of severe COPD should be multidisciplinary, focusing on respiratory therapies and nutritional support. Studies have shown that protein supplementation, such as collagen hydrolysate peptides, can improve muscle function and the quality of life of patients. This study aims to evaluate the impact of collagen supplementation in patients with severe COPD by recruiting 100 volunteers for the analysis of nutritional and hemodynamic parameters. The supplementation will occur over 3 months with pre- and post-treatment evaluations. If the hypothesis is confirmed, the product could fill a market gap by offering specific cardiovascular benefits for patients with severe COPD.